Identification of a retinoic acid-inducible gene I from Japanese eel (Anguilla japonica) and expression analysis in vivo and in vitro. (August 2016) - Feng, Jianjun; Guo, Songlin; Lin, Peng; Wang, Yilei; Zhang, Ziping; Zhang, Zaipeng; Yu, Lili
Abstract: RIG-I (retinoic acid inducible gene-I) is one of the key cytosolic pattern recognition receptors (PRRs) for the recognition of cytosolic viral nucleic acids and the production of type I interferons (IFNs). The full-length cDNA sequence of RIG-I ( Aj RIG-I) in Japanese eel ( Anguilla japonica ) was identified and characterized in this article. The full-length cDNA of Aj RIG-I was 3468 bp, including a 5′-untranslated region (UTR) of 52 bp, a 3′-UTR of 617 bp and an open reading frame (ORF) of 2799 bp encoding a polypeptide of 933 amino acid residues with a calculated molecular mass of 106.2 kDa. NCBI CDD analysis showed that the Aj RIG-I protein had the typical conserved domains, including two adjacent caspase activation and recruitment domains (CARDs), a DEXDc domain, a HELICc domain and a C-terminal regulatory domain (RD). Quantitative real-time polymerase chain reaction (qRT-PCR) analysis revealed a broad expression for Aj RIG-I in a wide range of tissues, with the predominant expression in liver, followed by the gills, spleen, kidney, intestine, skin, and the very low expression in muscle and heart. The Aj RIG-I expressions in liver, spleen and kidney were significantly induced following injection with LPS, the viral mimic poly I:C, and Aeromonas hydrophila infection. In vitro, the Aj RIG-I transcripts of Japanese eel liver cells were significantly enhanced by poly I:C and PGN stimulation, down-regulated with CpG-DNA treatment whereas no change of the expression level was found post LPS challenge. These results collectively suggested Aj RIG-I transcripts expression possibly play an important role in fish defense against viral and bacterial infection. Highlights: RIG-I gene from Japanese eel was cloned. In vivo, Aj RIG-I was up-regulated by LPS, poly I:C, and bacteria. In vitro, Aj RIG-I was enhanced by poly I:C and PGN.